1996
DOI: 10.1016/s0022-5347(01)66178-0
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Carcinoma in Children: The Detroit Experience

Abstract: Although renal cell carcinoma in childhood often presents at an advanced stage, the prognosis for those with isolated regional lymph node involvement appears to be encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1
8

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 23 publications
4
32
1
8
Order By: Relevance
“…Generally, nodal metastases, even in the absence of distant metastases, portend ominous prognosis in RCC patients (16). The characteristics of our two cases with nodal involvement (cases 1 and 2) were similar to those of certain pediatric RCC cases with isolated lymph node involvement in which prolonged survival was reported (10). Very recently, Geller et al (14) also reported that nodal disease without distant metastasis (TxN1-3M0) has a favorable short-term prognosis after surgery alone in Xp11 translocation RCC patients.…”
Section: Discussionsupporting
confidence: 78%
“…Generally, nodal metastases, even in the absence of distant metastases, portend ominous prognosis in RCC patients (16). The characteristics of our two cases with nodal involvement (cases 1 and 2) were similar to those of certain pediatric RCC cases with isolated lymph node involvement in which prolonged survival was reported (10). Very recently, Geller et al (14) also reported that nodal disease without distant metastasis (TxN1-3M0) has a favorable short-term prognosis after surgery alone in Xp11 translocation RCC patients.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly only 0.3% to 1.3% of all RCC present during childhood. 5 The suggests a clinical similarity between adult and pediatric RCC except that in children the sex ratio is equal, minor trauma frequently participates in the presentation (as observed in our patient), and there is increased survival of children with isolated lymph node involvement.…”
Section: Case Reportsupporting
confidence: 68%
“…It occurs primarily in middle-aged to elderly adults, with less than 1% of cases occurring below the age of 20 years [3,9]. Speculation exists as to whether RCC in children represents a different entity from its adult counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Previous retrospective studies of RCC in children [2,3,5,[15][16][17][18][19][20][21][22][23] collectively show a mean age at presentation of 9-11 years; a lack of a male predominance; a 30-60% incidence of pain, mass, and hematuria, with virtual absence of the triad of all three; and a 50-70% overall survival, with a dismal prognosis for metastatic disease. Our results were similar, but in addition, we found a higher frequency of paraneoplastic phenomena (31%); two patients with polycythemia, four with hypertension, one with fever, and one with weight loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation